A study on the vietnamese translational versions of comtemporary english works – a communicative perspective (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigated some strategies representing communicative approach to translation manifested in Vietnamese translational versions of contemporary English works. The theories of translation methods developed by Susan Bassnett and Mc. Guire, Catford, Hatim, B. and I. Mason, especially Peter Newmark were used to elicit data. The communicative translation requires both linguistic and socio-cultural knowledge. 800 samples serving as data were extracted from some contemporary English works and their Vietnamese translation versions. They were divided into 8 strategies making up communicative approach to translation. The strategies were categorized according to their features. Data were analyzed basing on linguistic knowledge, culture and social conventions. The results suggested that the frequency and preference of the strategies were not the same. Some of them were used more than others. In communicative translation, the translators focused the most on rearranging words, phrases or sentences compared with the original versions according to both objectively grammatical rules and translators’ subjective intention (30,5%). Next, the translators tried to clarify the source language text by adding some linguistic items to it or paraphrasing it; they even adapted cultural elements in the SL text to TL culture (17,6%). Besides, some grammatical adjustments were made so that the translational versions sounded natural and familiar to the TL readership (14,6%). Idiomatic translation occupied 11,2 %. Both sentence division and connective addition occupied 7,9%. During transferring process, the idiomatic, figurative form were converted into direct, non-figurative form (5,6%). The strategy occupying the least percentage was converting rhetorical question into assertion (3,7%).